2021
DOI: 10.1007/s40272-021-00449-z
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Children: NSAID Use in the Perioperative and Emergency Department Settings

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are often used for pediatric pain management in the emergency setting and postoperatively. This narrative literature review evaluates pain relief, opioid requirements, and adverse effects associated with NSAID use. A PubMed search was conducted to identify randomized controlled trials evaluating the use of conventional systemic NSAIDs as pain management for children in the perioperative or emergency department (traumatic injury) setting. Trials of cyclooxygenase-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…In addition to education, the use of NSAIDs also decreased the total number of opioid doses and duration of use in the study. These findings correlate with prior literature supporting the positive effects of nonopioid medications and multimodal pain management on decreasing opioid requirements, minimizing opioid-induced adverse events, and increasing patient satisfaction 22–25 . Results from a randomized controlled trial by the Canadian Medical Association of pediatric patients having minor outpatient orthopaedic surgery found equal improvements in pain scores with no difference in efficacy between oral morphine and ibuprofen for at-home pain control 26 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to education, the use of NSAIDs also decreased the total number of opioid doses and duration of use in the study. These findings correlate with prior literature supporting the positive effects of nonopioid medications and multimodal pain management on decreasing opioid requirements, minimizing opioid-induced adverse events, and increasing patient satisfaction 22–25 . Results from a randomized controlled trial by the Canadian Medical Association of pediatric patients having minor outpatient orthopaedic surgery found equal improvements in pain scores with no difference in efficacy between oral morphine and ibuprofen for at-home pain control 26 .…”
Section: Discussionsupporting
confidence: 83%
“…These findings correlate with prior literature supporting the positive effects of nonopioid medications and multimodal pain management on decreasing opioid requirements, minimizing opioid-induced adverse events, and increasing patient satisfaction. [22][23][24][25] Results from a randomized controlled trial by the Canadian Medical Association of pediatric patients having minor outpatient orthopaedic surgery found equal improvements in pain scores with no difference in efficacy between oral morphine and ibuprofen for at-home pain control. 26 This study also reported significant decreases in medicationrelated adverse events with the use of ibuprofen rather than morphine, again supporting the potential benefits of nonopioid medications in the 61% of patients in this study who reported opioid-associated side effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, ketorolac was studied in children mainly for post-operative pain and administered intravenously [ 18 ]. Only a few trials investigated its employment in a PED setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, ketorolac was studied in children mainly for post-operative pain and administered intravenously [19]. Only a few trials investigated its employment in a PED setting.…”
Section: Discussionmentioning
confidence: 99%